2006
DOI: 10.1017/s0022215106002763
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin resistant Staphylococcus aureus: is it a problem for nasal surgery?

Abstract: Methicillin resistant Staphylococcus aureus (MRSA) is becoming ever more prevalent in the UK, and the proportion of MRSA to methicillin sensitive Staphylococcus aureus (MSSA) seems to be increasing. New strains of MRSA are ever developing resistance to antibiotic treatment, increasing morbidity and mortality of infection. Staphylococcus aureus is part of the normal flora of the nose, and MRSA colonizes the nose in infection. However, nasal surgery is rarely complicated by staphylococcal infections, and MRSA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…MRSA infections following rhinoplasty are exceedingly rare according to the literature, but it is possible that these may be underdiagnosed or under‐reported. As noted in Sharma et al's review, the rarity of MRSA infections following rhinoplasty may be due to the fact that the population of patients undergoing the procedure are well outside of the at risk groups for MRSA colonization and infection, that is, younger patients without prior hospitalizations 17. Patients known to be at risk for MRSA colonization and thus infection after surgery include those who work in the healthcare setting (as well as their household members), patients over 60 years of age, those with recent hospital admission or antibiotic use, and patients with HIV 5, 8, 9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRSA infections following rhinoplasty are exceedingly rare according to the literature, but it is possible that these may be underdiagnosed or under‐reported. As noted in Sharma et al's review, the rarity of MRSA infections following rhinoplasty may be due to the fact that the population of patients undergoing the procedure are well outside of the at risk groups for MRSA colonization and infection, that is, younger patients without prior hospitalizations 17. Patients known to be at risk for MRSA colonization and thus infection after surgery include those who work in the healthcare setting (as well as their household members), patients over 60 years of age, those with recent hospital admission or antibiotic use, and patients with HIV 5, 8, 9…”
Section: Resultsmentioning
confidence: 99%
“…In a review by Sharma et al of MRSA and nasal surgery (including endoscopic sinus surgery), the authors found no reported cases of MRSA infections following septoplasty or rhinoplasty. The authors mention that it would be expected for these infections to occur, given that the surgical incision is made in a region of heavy staphylococcal colonization, and increasingly the strain is likely to be nosocomial MRSA 17. One reason they gave for the apparent lack of MRSA infections in these procedures may be the age of the patient, typically middle aged, relatively healthy, and without many previous hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
“…2 Indeed, MRSA nasal colonization is established in 4.2% of patients on admission and over 20% after an average-length hospitalization. 4 Health care workers are at increased risk of MRSA colonization. One recent study identified that 6.7% of healthcare workers were colonized with MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…These infectious complications include cellulitis, sinusitis, cavernous sinus thrombosis, septicemia, brain abscess, and toxic shock syndrome. 4,12 Yet, there are only two reports in the literature describing MRSA infections following rhinoplasty. Cabouli et al described a case of a culture-proven MRSA abscess developing at the inner canthus of a postrhinoplasty patient, attributed to infection of the external lateral osteotomy site.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, the incidence of nasal carriage of MRSA in intensive therapy units varies between 4.2 per cent on admission 21 to more than 20 per cent after an average stay, 22 especially in immunocompromised patients. 24 The aim of this study was to determine the incidence of MRSA infection in the peri-operative course of patients undergoing rhinological surgery. Some studies show an increase in conditions such as MRSA sinusitis.…”
Section: Introductionmentioning
confidence: 99%